Effect of sunlight exposure on phthalates migration from plastic containers to packaged juices - Rastkari, Noushin (J Environ Health Sci Eng, 2018)
BACKGROUND: Acidic juices such as lemon juice, vinegar and Verjuice are popular beverages regularly consumed by both children and adults. Various brands of different acidic juices in Iran markets are packaged in disposable plastic bottles. Some evidence suggests that phthalates may immigrate from plastic bottles. METHODS: In this research the influence of sunlight, type of container and storage time on the leaching of phthalates from packaging materials into selected juices was investigated, by analyzing the samples kept in different conditions, before and throughout 2, 4 and 6 months storage time. RESULTS: The mean phthalate concentrations of the examined samples were determined to be between <LOD and 0.521 μg/L in verjuice, <LOD and 0.261 μg/L in lemon juice, <LOD and 0.599 μg/L in vinegar. DEP and DEHP showed the highest level of migration into acidic juices packed in plastic bottles. CONCLUSIONS: Results of analyses before and after storage show that some storage conditions can increase the concentrations of DBP, DEHP and DEP in acidic juices. The results of this study indicate the possible leaching of phthalates from packages made of plastic materials into the contents.